Physical match demands of four LIQUI-MOLY Handball-Bundesliga teams from 2019–2022: effects of season, team, match outcome, playing position, and halftime - Saal, Christian; Baumgart, Christian; Wegener, Florian; Ackermann, Nele; Sölter, Florian; Hoppe, Matthias W. (Frontiers in Sports and Active Living, 2023)
Introduction Due to the development in team handball, there is a need to optimize the physical capacities of team handball players for which knowledge of the physical match demands is essential. The aim of this study was to investigate the physical match demands of four LIQUI-MOLY Handball- Bundesliga (HBL) teams across three seasons with respect to the effects of season, team, match outcome, playing position, and halftime. Methods A fixed installed local positioning system (Kinexon) was used, collecting 2D positional and 3D inertial measurement unit data at 20 Hz and 100 Hz, respectively. The physical match demands were operationalized by basic (e.g., distance, speed, and acceleration) and more advanced variables (e.g., jumps, throws, impacts, acceleration load, and metabolic power). A total of 347 matches (213 with an additional ball tracking) were analyzed from four teams (one top, two middle, and one lower ranked) during three consecutive seasons (2019-2022). One-way ANOVAs were calculated to estimate differences between more than two groups (e.g., season, team, match outcome and playing position). Mean differences between halftimes were estimated using Yuen’s test for paired samples. Results Large effects were detected for the season (ξˆ = 0.86), team (0.56 ≤ ξˆ ≤ 0.72), and playing position (0.64 ≤ ξˆ ≤ 0.98). Medium effects were found for match outcome (ξˆ ≤ .36) and halftime (ξˆ ≤ .47). Conclusion For the first time, we provide a comprehensive analysis of physical match demands in handball players competing in the LIQUI-MOLY Handball-Bundesliga. We found that physical match demands differ on that top-level with up to large effect sizes concerning the season, team, match outcome, playing position, and halftime. Our outcomes can help practitioners and researchers to develop team and player profiles as well as to optimize talent identification, training, regeneration, prevention, and rehabilitation procedures.